Field-driven electron photoemission via 3D-printed terahertz resonant vertical nanostructures - Rovere, Andrea; Piccoli, Riccardo; Bertoncini, Andrea; Jeong, Young Gyun; Payeur, Stephane; Vidal, Francois; Kwon, O. Pil; Lee, Seung Heon; Seok, Jin Hong; Morandotti, Roberto; Liberale, Carlo; Razzari, Luca (2021 Photonics North, PN 2021, 2021)
We investigated terahertz resonant gold nanocones for out-of-plane field-driven photoemission and compare their performance with a standard non-resonant nanotip.
Keywords: 3-D printing; 3D-printing; Array of THz nanocone; Electron photoemission; Nanocone; Out-of-plane; Performance; Tera Hertz; THz field-driven photoemission; THz fields; 3D printing; Array of THz nanocones; THz field-driven photoemission